Tracing Trends and Patterns of IKN Words in Media and Twitter: A Linguistic Corpus Study (Menelusuri Tren dan Pola Kata IKN di Media dan Twitter: Kajian Korpus Linguisti) - Devi Ambarwati Puspitasari; Kurniawan Kurniawan; Yenny Karlina; Hernina Hernina; Budi M Mulyo (Jurnal Gramatika, 2023)
This research focuses on the analysis of word trends and patterns associated with the "Ibu Kota Negara" (IKN) project, which involves relocating the capital city in Indonesia. The study examines these linguistic trends within the context of social media, specifically on Twitter, and a local media outlet, Tribun Kaltim. This type of research is descriptive qualitative using corpus linguistics methods. The research data is in the form of words, phrases and sentences originating from tweets with the hashtags #IbuKota Negara, #IKNNusantara, and #PindahIbuKota, as well as 100 selected news articles from Tribun Kaltim. The analysis was carried out with the help of corpus processing tools and focused on word list analysis, collocation, concordance checking, and exploration of plot features. The findings reveal noteworthy similarities in word trends and patterns across both datasets, indicating a certain degree of alignment between Indonesian conversations on Twitter and the reporting of news media. However, it is worth noting that Twitter conversations tend to exhibit a more dynamic and rapidly evolving nature compared to traditional news media reports. This study sheds light on the interconnectedness between social media discourse and traditional journalism in the context of the IKN project, offering valuable insights into public discourse dynamics in the digital age.